TAGE Score for Symptomatic Intracranial Hemorrhage Prediction After Successful Endovascular Treatment in Acute Ischemic Stroke. Issue 9 (14th June 2022) - Janvier, Paul; Kerleroux, Basile; Turc, Guillaume; Pasi, Marco; Farhat, Wassim; Bricout, Nicolas; Benzakoun, Joseph; Legrand, Laurence; Clarençon, Frédéric; Bracard, Serge; Oppenheim, Catherine; Boulouis, Grégoire; et al.
Abstract : Background: Determine if early venous filling (EVF) after complete successful recanalization with mechanical thrombectomy in acute ischemic stroke is an independent predictor of symptomatic intracranial hemorrhage (sICH) and integrate EVF into a risk score for sICH prediction. Methods: Consecutive patients with anterior acute ischemic stroke treated by mechanical thrombectomy issued from patients enrolled in the THRACE trial (Thrombectomie des Artères Cérébrales) and from 2 prospective registries were included and divided into a derivation (Center I; n=402) and validation cohorts (THRACE and center 2; n=507). EVF was evaluated by 2 blinded readers. sICH was defined according to the modified European cooperative acute stroke study II. Clinical and radiological data were analyzed in the derivation cohort (C1) to identify independent predictors of sICH and construct a predictive score test on the validation cohort (THRACE + C2). Results: Symptomatic ICH rate was similar between the two cohorts (9.9% and 8.9% respectively, P =0.9). Time from onset-to-successful recanalization >270 minutes (odds ratio [OR], 7.8 [95% CI, 2.5–24]), Alberta Stroke Program Early CT Score (≤5 [OR, 2.49 (95% CI, 1.8–8.1) or 6–7 [OR, 1.15 (95% CI, 1.03–4.46)]), glucose blood level >7 mmol/L (OR, 2.92 [95% CI, 1.26–6.7]), and EVF presence (OR, 11.9 [95% CI, 3.8–37.5]) were independent predictors of sICH and constituted the Time–Alberta Stroke Program Early CT–Glycemia–EVF score. Time–Alberta Stroke Program Early CT–Glycemia–EVF score was associated with an increased risk of sICH in the derivation cohort (OR increase per unit, 1.99 [95% CI, 1.53–2.59]; P <0.001) with area under the curve, 0.832 [95% CI, 0.767–0.898]. The score had good performance in the validation cohort (area under the curve, 0.801 [95% CI, 0.69–0.91]). Conclusions: Time–Alberta Stroke Program Early CT–Glycemia–EVF score is a simple tool with readily available clinical variables with good performances for sICH prediction after mechanical thrombectomy. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01062698.